Managing green-burbia: utilising urban management practices to address the Urban Heat Island as a call to adapt to climate change impacts - the case of Melville in Johannesburg - Elbertse, Caspar (My University, 2021)
Suburban areas are considered major contributors to the Urban Heat Island Effect (UHIE) and climate change due to their high consumption levels. This has a greater impact on lower-income communities than suburbia. This research report argues the City of Johannesburg lacks alignment between climate change policies and requires looking at an urban management model to resolve this. This research investigates the best way for suburbs to reduce their impact on the UHIE through urban management practices and tools to help streamline it into policy. Residents responded to an online questionnaire, sent through social media sites, on the UHIE and how they have adapted to its effects. The results indicate knowledge of the UHIE and climate change influence a resident’s chances of implementing adaptation measures. An urban management model incorporating the needs of residents will require inclusive, participatory and resilient characteristics
A research report submitted to the School of Architecture and Planning, Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Urban Studies in Urban Management, 2021